Recent Developments of Reflectarray Antennas in Dual-Reflector Configurations - Carolina Tienda; Manuel Arrebola; José A. Encinar (International Journal of Antennas and Propagation)
Recent work on dual-reflector antennas involving reflectarrays is reviewed in this paper. Both dual-reflector antenna with a reflectarray subreflector and dual-reflectarrays antennas with flat or parabolic main reflectarray are considered. First, a general analysis technique for these two configurations is described. Second, results for beam scanning and contoured-beam applications in different frequency bands are shown and discussed. The performance and capabilities of these antennas are shown by describing some practical design cases for radar, satellite communications, and direct broadcast satellite (DBS) applications.